Constrained Plott Equilibria, Directional Equilibria and Global Cycling Sets - Cohen, L.; Matthews, S. (Review of Economic Studies, 1980)
Linda Cohen, Steven Matthews; Constrained Plott Equilibria, Directional Equilibria and Global Cycling Sets, The Review of Economic Studies, Volume 47, Issu